Manajemen Kesiswaan Pada Madrasah Tsanawiyah An- Nawawi 01 BERJAN Purworejo - Isnaini , Isnaini (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
Application of student management in educational institutions in one of the necessities to improve the quality of education. Lack of cooperation with teachers is an obstacle in effective student management. This study aims to determine the planning, implementation, monitoring, and evaluation of student management programs. The method used in this research is descriptive method with a qualitative approach. Data collection techniques using observation techniques, interviews, and documentation. Research subjects are the principal, teachers, and students MTs An-Nawawi Berjan Purworejo. The results showed that the student management planning was prepared by the student himself and the principal of the madrasah. The implementation of student management is adjusted to the needs and level of development of new student. Student management supervision has made efforts to organize new students well, so that there is no overlap and time waste in the student management process in the classroom. Evaluation is carried out to improve activities related to student management.